PROBLEMATIKA PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN PEMENUHAN HAK NAFKAH - Hanafi, Aisyah Ayunda (Law Study Program, Faculty of Law, Nusantara Islamic University, 2023)
Abstract Marriage is a bond that involves rights and obligations, one of which is the obligation to provide maintenance to children. This study aims to determine the legal protection of children as victims of the fulfillment of the right to support by their parents and to find out the efforts and obstacles to the protection of children as victims of children's rights. This research uses normative juridical method, which combines analysis of laws and regulations with data collection through interviews with resource persons from LPA Bandung City. The results of this study indicate that there are still many parents who do not provide for their children. Of course this is caused by several factors such as divorce, economic problems, poor health of parents, and lack of understanding of parents regarding the obligation to provide for their children. Although the law has regulated the obligation of maintenance, the implementation of the law is still constrained by the lack of evidence and the slow legal process. It is suggested that in dealing with cases of children from unregistered marriages, innovative legal solutions such as mediation or community-based approaches are needed, to ensure children's rights are still fulfilled despite administrative obstacles. Preventive efforts through education on children's rights and family responsibilities in the school curriculum are also important. With this approach, it is hoped that future communities will be more concerned about the fulfillment of children's rights, both as a legal obligation and a shared moral responsibility. Keywords: child maintenance, divorce, children's rights, legal protection, law enforcement Abstrak Pernikahan merupakan ikatan yang melibatkan hak dan kewajiban, salah satunya adalah kewajiban memberikan nafkah kepada anak. Penelitian ini bertujuan untuk mengetahui perlindungan hukum terhadap anak sebagai korban pemenuhan hak nafkah oleh orang tuanya dan untuk mengetahui upaya serta kendala terhadap perlindungan anak sebagai korban hak anak. Penelitian ini menggunakan metode yuridis normatif, yang menggabungkan analisis terhadap peraturan perundang-undangan dengan pengumpulan data melalui wawancara dengan narasumber dari LPA Kota Bandung. Hasil penelitian ini menunjukan bahwa masih banyak orang tua yang tidak menafkahi anaknya. Tentu saja hal ini disebabkan oleh beberapa faktor seperti perceraian, masalah ekonomi, kesehatan orang tua yang buruk, dan kurangnya pemahaman orang tua mengenai kewajiban untuk menafkahi anaknya. Meskipun Undang-undang telah mengatur kewajiban nafkah, implementasi hukum masih terkendala oleh minimnya bukti dan lambatnya proses hukum. Saran dari penelitian ini, dalam menangani kasus anak-anak hasil pernikahan yang tidak tercatat, diperlukan solusi hukum inovatif seperti mediasi atau pendekatan berbasis komunitas, untuk memastikan hak anak tetap terpenuhi meskipun ada kendala administratif. Upaya preventif melalui pendidikan tentang hak anak dan tanggung jawab keluarga dalam kurikulum sekolah juga penting. Dengan pendekatan ini, diharapkan masyarakat masa depan lebih peduli terhadap pemenuhan hak anak, baik sebagai kewajiban hukum maupun tanggung jawab moral bersama. Kata kunci: nafkah anak, perceraian, hak anak, perlindungan hukum, penegakan hukum